Implementation of the Asymmetric Fountain Code Algorithm to Secure Aviation Licensing and Regulatory Document Data - Daniel D Rumani (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Several agencies, both government and private, require the security of personal data, especially as this information can only be accessed or transmitted to authorized people or organizations. Likewise with license and regulatory records, these materials are exceedingly confidential. Documents pertaining to permissions and regulations issued by aviation authorities, such as operating permits and aircraft certification, However, the difficulty is that when data is distributed using an internet connection, it can slip into the hands of unscrupulous people. Implementation of the Asymmetric Fountain Code Algorithm to safeguard confidential text data is used to safeguard license and regulatory document data with encryption and description methods using the Fountain Code Algorithm, which has two keys to access plaintext and ciphertext documents using SharpDevelop 5.1 software in the C# language. This research reveals that the outputs of the Fountain Code algorithm can restore plaintext data in its entirety. So it can be inferred that the asymmetric Fountain Code algorithm meets good data integrity and is safe; the complexity of the algorithm is simpler; and the amount of plaintext is exactly related to time.